(untitled) (Biological Sciences - PJSIR, 1996)
To evaluate the relative importance of fungal species, the known varieties of mustard/rapeseed collected from various research institutes located throughout Pakistan, were investigated. Alternaria species were the predominant fungiisolatedfromthesamplesoffreshly harvestedcrops.ThetoxinproducingpotentialofvariousstrainsofAlternaria alternata wasinvestigated. The maximumamountproduced by theseisolates was 27.5mglkgfor tenuazonic acid and 22.9 mglkg for altematriol monomethyl ether.